2019
DOI: 10.5892/ruvrd.v17i1.5051
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DA ATIVIDADE ENZIMÁTICA DE FUNGO ENDOFÍTICO ISOLADO DE Annona crassiflora (MAROLO) COM INTERESSE BIOTECNOLÓGICO

Abstract: Os micro-organismos endofíticos são fungos e bactérias encontrados no interior de tecidos e órgãos saudáveis das plantas e que não causam danos aparentes aos hospedeiros durante o ciclo vital in vivo. Os fungos endofíticos são capazes de produzir substâncias de interesse biotecnológico, sendo que algumas enzimas possuem aplicações em processos industriais. A espécie Annona crassiflora, conhecida popularmente como marolo ou pinha do cerrado, é uma árvore nativa e exclusiva do cerrado brasileiro, amplamente difu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In recent years, studies have shown that soil microorganisms, through the production of organic acids, can accelerate the release of nutrients from these rocks, increasing availability in the soil solution for plant absorption (Moreira;Siqueira, 2006). Several studies have emphasized the selection of phosphate solubilizing microorganisms (Massenssini et al, 2016;Schueler;Dourado;Rizzo, 2019;Terra et al, 2019), and presented promising data on the potential for application in the field (Dabaja et al, 2019;Souza et al, 2017;Terra et al, 2019). Thus, these microorganisms are biotechnological alternatives that can enable the use of natural phosphate from national deposits, such as Araxá and Catalão natural phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that soil microorganisms, through the production of organic acids, can accelerate the release of nutrients from these rocks, increasing availability in the soil solution for plant absorption (Moreira;Siqueira, 2006). Several studies have emphasized the selection of phosphate solubilizing microorganisms (Massenssini et al, 2016;Schueler;Dourado;Rizzo, 2019;Terra et al, 2019), and presented promising data on the potential for application in the field (Dabaja et al, 2019;Souza et al, 2017;Terra et al, 2019). Thus, these microorganisms are biotechnological alternatives that can enable the use of natural phosphate from national deposits, such as Araxá and Catalão natural phosphate.…”
Section: Introductionmentioning
confidence: 99%